Whether Service Quality, Price and Location Can Increase Purchasing Decisions for Mobile Phones and Accecories - Desy Yanti Anggreni; Sri Sarbini; Wahyoe Herlyana Dewi; Karjono Karjono; Samsul Hadi; Nurul Qomariah (International Journal of Management Science and Information Technology, 2023)
The need for smartphones and their accessories is currently increasing significantly with the community's need for smartphones and accessories. This study aims to determine and analyze the effect of service quality, price and location on purchasing decisions for mobile phones and accecories at "Toko Eferata" Bondowoso. The population in this study are all consumers who have made transactions at "Elfrata Store" Bondowoso. The number of samples used in this study was 40 respondents on the basis that regional level research could be carried out with a number of N>30. The sampling method uses purposive sampling. using saturated sampling method. Data collection was carried out by distributing questionnaires. Analysis technique, where the respondents are those who have made purchases twice at the store. Data analysis used multiple linear regression analysis with the help of SPSS software. The results showed that location and price partially influence purchasing decisions and service quality does not partially affect purchasing decisions. Furthermore, the Adjusted R Square result is 31.6%. This shows that the ability of location, price and quality of service to explain purchasing decisions is only 31.6%, while 63.9% is explained by other things not examined.